EVALUASI KINERJA LEMBAGA PEMBERDAYAAN MASYARAKAT DESA UNTUK MENINGKATKAN POTENSI DESA (STUDI PADA DESA BLANKAHAN KECAMATAN KUALA KABUPATEN LANGKAT TAHUN 2013) - Minarni UMA (PERSPEKTIF, 2016)
Village within the framework of regional development goals is seen as an object to be built. Rural development will have implications on the progress of the region so that the concentration of rural development in the various approaches becomes important to be improved. This study aims to look at how the performance of the Institute of Rural Community Empowerment (LPMD) Blankahan Village District of Kuala Langkat Potential Increase in 2013 in the Village. This type of research is qualitative descriptive method. Source data used through interviews, literature study and documentation. Research results obtained some findings of which is the Institute's role as a facilitator of Rural Community empowerment is low this can be seen from the community participation in determining priority program proposals to be made respectively. This is evident from the results of the interview by the chairman of the village LPMD Blankahan that in determining community priorities proposed meeting attended and participated only listened but no coment. LPMD people assume can not do anything.